2017
DOI: 10.1038/s41698-017-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Ref-1-APE1 node in cancer signaling and other diseases: from bench to clinic

Abstract: Reduction-oxidation factor 1-apurinic/apyrimidinic endonuclease (Ref-1/APE1) is a critical node in tumor cells, both as a redox regulator of transcription factor activation and as part of the DNA damage response. As a redox signaling protein, Ref-1/APE1 enhances the transcriptional activity of STAT3, HIF-1α, nuclear factor kappa B, and other transcription factors to promote growth, migration, and survival in tumor cells as well as inflammation and angiogenesis in the tumor microenvironment. Ref-1/APE1 is activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
153
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(156 citation statements)
references
References 275 publications
(321 reference statements)
3
153
0
Order By: Relevance
“…Further analysis into the viability of the mitochondrial dysfunction and other affected pathways identified in this study as potential APE1‐based combination therapy targets is ongoing. Additionally, these results support the role of APE1 as a node in cancer signaling (Shah et al ., 2017). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis into the viability of the mitochondrial dysfunction and other affected pathways identified in this study as potential APE1‐based combination therapy targets is ongoing. Additionally, these results support the role of APE1 as a node in cancer signaling (Shah et al ., 2017). …”
Section: Discussionmentioning
confidence: 99%
“…ITGA1, part of the integrin signaling and virus entry via endocytic pathways as identified by IPA, is involved in cell proliferation (Macias‐Perez et al ., 2008) and invasion (Yang et al ., 2015), as well as inflammation (Becker et al ., 2013) and fibrosis (Ramos et al ., 2012), which have all been previously linked to APE1 (Aamann et al ., 2016; Shah et al ., 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Exposure to ionizing radiation or platinum compounds causes DNA damage that leads to formation of reactive oxygen species (ROS), which stimulate AP endonuclease activity. This leads to an increased expression of Ape1/Ref‐1 . It was observed that the cancer cells with primary or secondary resistance to the DNA damaging agents have an overexpression of Ape1/Ref‐1.…”
Section: Targeting Ccsc For Therapeutic Gainmentioning
confidence: 99%
“…Hence, Ape1/Ref‐1 can be responsible for primary resistance in patients. Studies show that p53‐regulated Ape1/Ref‐1 and ROS are crucial in the self‐renewal, differentiation, and survival of CSCs (Figure ) …”
Section: Targeting Ccsc For Therapeutic Gainmentioning
confidence: 99%
See 1 more Smart Citation